Wilcoxon's Method in Determining The Effect of Using Discovery Learning Learning Strategies on The Learning Outcomes Of Vocational Basic DPIB Grade X Students. - Suharry; Ambiyar; Mahesi Agni Zaus (AKADEMI TEKNIK ADI KARYA, 2024)
One of the Discovery Learning Learning strategies is one of the efforts made by teachers to improve student learning outcomes by providing opportunities for students to learn on their own from various sources they like. The purpose of this study is to determine the effect of using discovery learning strategies on learning outcomes. In this study, the author used an experimental method with a type of quantitative research using SPSS which focuses on the Wilcoxon test to analyze data and answer research results. The respondents in this study amounted to 35 DPIB grade X students at SMK Negeri 2 Sungai Penuh. Based on the results of the Wilcoxon test, the results of Asymp Sig 0.0 2 where < of 0.05 means that this indicates that there is an influence of the use of discovery learning strategies on the learning outcomes of Basic Vocational Education of grade X DPIB students.